Endometrioid adenocarcinoma of the colon arising from rare malignant transformation of extra-gonadal endometrioma - Anne Stoklosa; Youngeun Armbuster; Lila Marshall; Jamie L McDowell; Naixin Zhang; Ashlee Smith; Cynthia Angel; Aaron Varghese; Wei Huang; Richard Moore (Gynecologic Oncology Reports)
Background: Endometriosis is a common condition with a rare malignant potential. We report a case of a patient with a colon mass who underwent surgery for malignant endometriosis associated cancer.Case: A 70-year-old woman with a pelvic mass who was lost to follow-up for 6 years represented with an enlarging pelvic mass involving the sigmoid colon. The patient underwent colonoscopy which revealed atypical endometrial-type glandular proliferation. She then underwent exploratory laparotomy with total abdominal hysterectomy, bilateral salpingo-oophorectomy, rectosigmoid resection, and creation of end colostomy. Final pathology revealed endometrioid adenocarcinoma arising from colon serosal endometriosis. Observation or systemic chemotherapy were considered, and patient opted for observation. Conclusion: We report a case of malignant intestinal endometriosis. There is limited evidence to support a standardized approach to treatment due to the rare nature of this disease; the patient opted for observation. By understanding the presentation, diagnostic workup, and outcomes of each patient with malignant endometriosis, future research can be guided to ultimately improve patient outcomes.